Kecenderungan Penelitian Skripsi Mahasiswa Sekolah Tinggi Agama Islam Negeri Jember: Research Trends in Undergraduate Theses at the State Islamic Institute of Jember - Ahmad Mutohar (Fenomena, 2003)
The low quality and high prevalence of thesis completion issues among Islamic higher education students in Indonesia signal an urgent need to examine their research tendencies. This study investigates the research tendencies of undergraduate students at STAIN Jember across four key aspects: research focus, methodological approach, data analysis technique, and adherence to research timelines. A qualitative descriptive approach was employed, with documentation as the primary data collection method, supplemented by observation and interviews. A sample of 295 theses from the 1995/1996, 1996/1997, and 1997/1998 academic years was analyzed using percentage-based classification. The findings reveal a strong preference for formal educational institutions as research settings (55.59%), a dominant use of quantitative approaches (50.50%) over qualitative ones (25.42%), and a prevailing reliance on statistical analysis (74.58%), particularly Yule’s Q and Chi-square techniques, rather than logic-based descriptive methods. Furthermore, 57.28% of students completed their research on time, though delays remain significant. The study concludes that thesis supervision and the curriculum should be restructured to encourage methodological diversity, strengthen qualitative research competence, and enforce timeline discipline among students and advisors alike. Rendahnya kualitas dan tingginya prevalensi masalah penyelesaian skripsi di kalangan mahasiswa perguruan tinggi Islam di Indonesia menandakan perlunya kajian mendalam tentang kecenderungan penelitian mereka. Penelitian ini menyelidiki preferensi mahasiswa STAIN Jember dalam empat aspek: fokus penelitian, pendekatan metodologis, teknik analisis data, dan kepatuhan terhadap jadwal penelitian. Pendekatan deskriptif kualitatif digunakan dengan dokumentasi sebagai teknik utama, serta observasi dan wawancara sebagai pendukung. Sebanyak 295 skripsi dari tahun akademik 1995/1996, 1996/1997, dan 1997/1998 dianalisis menggunakan teknik persentase. Hasil menunjukkan kecenderungan kuat pada lembaga pendidikan formal sebagai fokus penelitian (55,59%), dominasi pendekatan kuantitatif (50,50%) dibanding kualitatif (25,42%), serta preferensi tinggi terhadap analisis statistik (74,58%), terutama teknik Yule’s Q dan Chi-kuadrat, ketimbang analisis deskriptif berbasis logika. Sebanyak 57,28% mahasiswa menyelesaikan penelitian tepat waktu, meskipun keterlambatan masih signifikan. Penelitian ini merekomendasikan restrukturisasi bimbingan dan kurikulum untuk mendorong keragaman metodologis, penguatan kompetensi penelitian kualitatif, serta penegakan disiplin waktu.